Sleep quality, daytime sleepiness and health-related quality-of-life in maintenance haemodialysis patients. (June 2016) - Shen, Quanquan; Huang, Xiaohong; Luo, Zhaofen; Xu, Xiujun; Zhao, Xiang; He, Qiang
Objectives: To assess the relationship between sleep quality, daytime sleepiness and health-related quality-of-life (HRQoL) in Chinese patients undergoing maintenance haemodialysis (MHD). Methods: This cross-sectional study enrolled patients undergoing MHD. Self-reported sleep quality (Pittsburgh Sleep Quality Index [PSQI]), daytime sleepiness (Epworth Sleepiness Scale [ESS]) and HRQoL (36-item Short Form [SF-36]) were recorded for all patients. Results: Sixty eight patients (mean ± SD age = 61.75 ± 16.56 years; 43 male/25 female) who regularly received MHD were included. The prevalence of poor sleepers was 69.1% (47/68) and daytime sleepiness was 11.8% (eight of 68). Poor sleepers had a significantly lower Physical Component Scale (PCS) score, Mental Component Scale (MCS) score and total SF-36 score than good sleepers. The PSQI score correlated inversely with both the PCS and MCS scores and correlated positively with age. Independent variables associated with total SF-36 score were duration of MHD, ESS score and PSQI score. Conclusions: Poor sleep quality is a common and severe issue for MHD patients in east China. Both sleep quality and daytime sleepiness were associated with lower HRQoL scores.